Hand Posture Mouse. (2015) - Grif, Horatiu-Stefan; German, Zoltan; Gligor, Adrian
Abstract: The goal of this paper is to improve the recognition of the hand postures used in a Human Computer Interaction interface for controlling the mouse cursor. The paper proposes a new and useful feature for recognition of the human hand postures, an algorithm which uses this feature for controlling the mouse cursor and an algorithm for hand color skin calibration. The main benefit of the proposed hand feature is the low sensitivity to illuminace level changes. Using the proposed algorithms and hand feature the authors have developed an application which presents a good behavior in presence of the daylight changes and have a good behavior in a large range of illuminance levels starting from the high levels (gives by the daylight from the midday) to low levels (gives by the daylight from the twilight).